Sulfur mustard-induced epigenetic modifications over time − a pilot study. (1st September 2018) - Simons, Thilo; Steinritz, Dirk; Bölck, Birgit; Schmidt, Annette; Popp, Tanja; Thiermann, Horst; Gudermann, Thomas; Bloch, Wilhelm; Kehe, Kai
Highlights: Epigenetic modifications are discussed to cause SM-induced long-term effects. Early endothelial cells were exposed to low SM concentrations (0.5 and 1.0 mM). DNA methylation and histone modifications were assessed over time (6 cell passages). A human sample, obtained 1 year after an accidental SM exposure, was analyzed. SM had minor effects on histones, but an increase of DNA-methylation was found. Abstract: The chemical warfare agent sulfur mustard (SM) can cause long-term health effects that may occur even years after a single exposure. The underlying pathophysiology is unknown, but epigenetic mechanisms are discussed as feasible explanation. "Epigenetics" depicts regulation of gene function without affecting the DNA sequence itself. DNA-methylation and covalent histone modifications (methylation or acetylation) are regarded as important processes. In the present in vitro study using early endothelial cells (EEC), we analyzed SM-induced DNA methylation over time and compared results to an in vivo skin sample that was obtained approx. one year after an accidental SM exposure. EEC were exposed to low SM concentrations (0.5 and 1.0 μM). DNA methylation and histone acetylation (H3-K9, H3-K27, H4-K8) or histone di-methylation (H3-K9, H3-K27, H3-K36) were investigated 24 h after exposure, and after 2 or 4 additional cell passages. The human skin sample was assessed in parallel. SM had only some minor effects on histone modifications. However, a significant and pronounced increase of DNA methylation was detected in the late cell passages as well as in the skin sample. Our results indicate that SM does indeed cause epigenetic modifications that appear to persist over time.